Phytochemical investigation and in vitro anthelmintic evaluation of extracts of Wild Cinchona (Neolamarckia cadamba Roxb.) fruits - Kumar, Praveen; Tripathi, Laxmi; Verma, Amita (Mongolian Journal of Chemistry, 2023)
Neolamarckia cadamba Roxb., a plant commonly used in Indian traditional medicines, has been recognized for its anthelmintic properties. This study aimed to evaluate the in vitro anthelmintic activity of N. cadamba fruit extracts against Ascaridia galli (roundworm), Raillietina spiralis (tapeworm), and Pheretima posthuma (Indian adult earthworm). The hydro-methanolic extract of N. cadamba fruits exhibited superior anthelmintic activity compared to the ethyl acetate extract. Phytochemical analysis of the extracts revealed the presence of phenols, tannins, saponins, glycosides, phytosterols, flavonoids, and terpenoids. Furthermore, the contents of phenolics, flavonoids, proanthocyanidins, and anthocyanins in the fruit extracts were quantified. The quantitative analysis of total phenolic content of extracts revealved that hydromethanolic extract contains higher quantity of phenolics, flavonoids, proanthocyanidins, and anthocyanins in comparision to the ethylacetate extract. These findings support the observation that hydro-methanolic extract of N. cadamba fruits exhibited superior anthelmintic activity compared to the ethyl acetate extract because polyphenolic compounds are well established for their anthelmintic activity.